An Integrated Approach to Land Condition Mapping:Combining Terrestrial Surveys, Photogrammetry, and GIS for Data Center Development in Nongsa Special Economic Zone - Irawan, Sudra; Anggoro, Prastiwo; Pratama, Rizki Widi; Rassarandi, Farouki Dinda; Nainggolan, Marsanda; Basri, Muhammad Adi Hasan; M. Rajab Al Hakim; Sembiring, Fridheani Reshana; Simanjuntak, Pernando; Artini, Tia; Aji, Satriya Bayu (Journal of Geoscience, Engineering, Environment, and Technology, 2025)
Accurate and comprehensive land condition mapping is crucial for infrastructure development planning, particularly for data center construction in Nongsa Special Economic Zone (SEZ). This research integrates terrestrial survey, photogrammetry, and geographic information system (GIS) data to produce optimal land condition maps. The methodology involves field data collection through terrestrial measurements, aerial photography using photogrammetry, and data processing/analysis using GIS tools. This integrated approach enables the creation of comprehensive land condition maps, incorporating topography, land use, and other supporting parameters. The results demonstrate improved mapping accuracy and detailed spatial information, supporting informed location decisions. Eleven thematic maps were created, including topography, longitudinal and transverse profiles, composite volume, DSM/DTM contours, land cover, soil type, slope, water density, and flood hazard maps. Flood hazard analysis reveals that Nongsa has low (1.13 km²), moderate (61.16 km²), high (34.32 km²), and very high (0.0078 km²) flood risk areas. The majority of Nongsa (61.16 km²) falls within the moderate flood risk category. This research identifies that a significant portion of Nongsa, specifically 61.16 km², is categorized as having a moderate flood risk, highlighting the need for targeted infrastructure planning and risk mitigation strategies in the development of data centers within the SEZ. The results of this study also provide important insights into the impact of land use changes on the local ecosystem, making them valuable for planning more environmentally friendly and sustainable development.